Targeted RNAseq of Formalin-Fixed Paraffin-Embedded Tissue to Differentiate Among Benign and Malignant Adrenal Cortical Tumors - Plaska, Samuel W.; Liu, Chia-Jen; Lim, Jung Soo; Rege, Juilee; Bick, Nolan R.; Lerario, Antonio M.; Hammer, Gary D.; Giordano, Thomas J.; Else, Tobias; Tomlins, Scott A.; Rainey, William E.; Udager, Aaron M. (Hormone and Metabolic Research, 2020)
Lack of routine fresh or frozen tissue is a barrier to widespread transcriptomic analysis of adrenal cortical tumors and an impediment to translational research in endocrinology and endocrine oncology. Our group has previously pioneered the use of targeted amplicon-based next-generation sequencing for archival formalin-fixed paraffin-embedded (FFPE) adrenal tissue specimens to characterize the spectrum of somatic mutations in various forms of primary aldosteronism. Herein, we developed and validated a novel 194-amplicon targeted next-generation RNA sequencing (RNAseq) assay for transcriptomic analysis of adrenal tumors using clinical-grade FFPE specimens. Targeted RNAseq-derived expression values for 27 adrenal cortical tumors, including aldosterone-producing adenomas (APA; n=8), cortisol-producing adenomas (CPA; n=11), and adrenal cortical carcinomas (ACC; n=8), highlighted known differentially-expressed genes (DEGs; i. e., CYP11B2, IGF2, etc.) and tumor type-specific transcriptional modules (i. e., high cell cycle/proliferation transcript expression in ACC, etc.), and a subset of DEGs was validated orthogonally using quantitative reverse transcription PCR (qRT-PCR). Finally, unsupervised hierarchical clustering using a subset of high-confidence DEGs revealed three discrete clusters representing APA, CPA, and ACC tumors with corresponding unique gene expression signatures, suggesting potential clinical utility for a transcriptomic-based approach to tumor classification. Overall, these data support the use of targeted amplicon-based RNAseq for comprehensive transcriptomic profiling of archival FFPE adrenal tumor material and indicate that this approach may facilitate important translational research opportunities for the study of these tumors.
Keywords: next-generation sequencing (NGS); quantitative reverse-transcription polymerase chain reaction (qRT-PCR); aldosterone-producing adenoma (APA); cortisol-producing adenoma (CPA); adrenal cortical carcinoma (ACC); FFPE